Hala Tuju Pendidikan Teknik dan Vokasional: Integrasi Kaedah Avicenna dan Konsep Pendidikan untuk Semua. (Sains Humanika, 2011)
Education system nowadays had not gone through a simple phase and process anymore, but becoming much more complicated each day. With the existence of so many understanding and ideology in education, the ambience of education and the design of school curriculum become much more complex. Indeed, the destiny of education exist in various faces and shape until so many people get confuse and having an unclear vision of education. This article discuss about the destiny of education that exist in Education for All (EFA), the destiny of education by Avicenna and the relationship with Technical and Vocational Education and Training (TVET) in Malaysia briefly. The exploration process try to discover a meeting point between the global objectives in education today, and this classic Islamic philosopher view, and transform into a contemporary form to lead the development of the country. By referring to the national philosophy of education aims which is to develop a balance individual in physical, emotional, soul and intellect potentials, this article has been written with the purpose to give an alternative philosophy as a guidance that is much more closer with the atmosphere and believedsystem in Malaysia.
Keywords: Education for All (EFA); Avicenna; Destiny of Technical and Vocational Education and Training (TVET)